Implementasi Metode Mind Mapping Guna Meningkatkan Prestasi Belajar Pada Mata Pelajaran Akhidah Akhlak Kelas XIIS MAN 4 Kediri - Wildan Habibi; Samrotul Jannah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The teacher occupies an important position and determines the success of the achievement of goals in a learning process. Choosing the right learning method is something that needs to be considered by teachers. With this method of mind mapping can improve student learning achievement. Based on this, research was conducted with the title application of Mind Mapping Learning Methods to Improve Student Learning Achievement in Fiqh Subjects Class X IIS at MAN 4S Kediri Year of Study 2021/2022. The purpose of the research in this thesis is to find out the learning achievement of students of class X IIS akhidah akhlak subjects in MA Sunan Gunung Jati Gurah Kediri after the application of Mind Mapping learning methods is given. The research subject was a student of class X IIS MAN 4 Kediri as many as 36 students. The data collection procedure is through student learning outcome tests, student activity observation sheets, and the dissemination of student response questionnaires. The approach in this study uses a qualitative approach, because with a qualitative approach researchers can decipher the data obtained. The study used class-action research that lasted for two cycles and preceded pre-cycles. Based on the results of cycle 1 and cycle 2 by looking at data from the pre-cycle, data can be obtained that, students who have not completed in pre-cycle reached 36,1% or 13 students from 36 students. While the completed amounted to 63,8% or 23 students. While in cycle I has increased to 16,6% or 6 students who have not reached completion, and 83,3% or 30 students have achieved completion.